DETERMINATION OF THE DIRECTION OF RESEARCH ON THE DEVELOPMENT OF FIBER WASTE CLEANING TECHNOLOGICAL EQUIPMENT - Ulugbek Mamitbekovich, Muminov; Guzalkhan Usupjonovna, Muminova (Journal of Higher Education and Academic Advancement, 2024)
Objective: The study aims to develop an efficient fiber waste cleaning equipment design for the cotton processing industry. This design seeks to address current challenges, such as the inconsistent density of raw cotton and the resulting high levels of impurities in the fiber waste. Methods: A systematic approach is adopted, involving a literature review of existing cleaning systems, identification of key issues, and the development of a cleaning equipment design using a screw conveyor mechanism. The study optimizes operational parameters, including auger pitch, pile length, and mesh configuration, and evaluates the feasibility of the proposed equipment. Results: The research identified that inconsistencies in raw cotton density were a major cause of fiber defects. Existing cleaning machines were found to be ineffective in achieving complete impurity removal, often resulting in fiber loss. The proposed design, featuring a screw conveyor and mesh net, is expected to enhance cleaning efficiency by optimizing these parameters. Novelty: The study introduces a new approach to cotton fiber waste cleaning by using a screw conveyor design, which improves the separation of small impurities. The research also explores the feasibility of using a belt conveyor for waste transfer, contributing to more effective cotton waste management.